Investigation of Sway Back Posture Prevalence and Alignment of Spine and Lower Limb Joints in This Deformity - Leila Simorgh (Journal of Rehabilitation, 2006)
Objective: Sway Back posture is one of the most common postural deformity.This study aimed to define Sway back posture prevalence and quantitatively meassure of the joints alignment in it.